Litter Decomposition of Imperata cylindrica in a Copper Tailing Areas With Different Restoration History: Fungal Community Dynamics and Driving Factors - Jia, Tong; Wang, Xuerong; Guo, Tingyan; Chai, Baofeng (Frontiers in Microbiology, 2021)
Microorganisms drive litter decomposition while maintaining the chemical cycle of ecosystems. We used the dominant vegetation (Imperata cylindrica) in the mining area selected for this study for this experiment to explore fungal community characteristics, key fungal groups, and their associative driving factors during I. cylindrica litter decomposition. Maximum litter C/N values occurred 100 days after the commencement of the decomposition experiment during all different recovery years in this copper tailings area. Heavy metals in litter (copper [Cu], zinc [Zn], plumbum [Pb], and cadmium [Cd]) accumulated gradually with decomposition. The dominant fungal phyla observed in the community were Ascomycota and Basidiomycota, while the classes Sordariomycetes and Eurotiomycetes significantly increased as litter decomposition progressed. Degrees of connectivity and interaction between fungal communities were highest during the early litter decomposition stage. Sordariomycetes, Dothideomycetes, and Leotiomycetes all played critical roles in maintaining fungal community relationships. The effect of physicochemical properties and enzyme activities in I. cylindrica litter was significant on the dominant fungi while driving factors that affected fungal communities differed over different recovery stages. Total nitrogen (TN), heavy metals, pH, and enzyme activities in the little were significantly correlated to fungal community composition. Litter properties throughout the litter decomposition process mainly affected the dynamics of the fungal community structure. The main environmental factors that affected fungal community structure were copper content and pH. Dichotomopilus, Trichoderma, Knufia, Phialophora, Oxyporus, and Monocillium, which all played important roles in litter decomposition, positively correlated to heavy metals, sucrase, and catalase. Finally, results from this study will help us better clarify litter decomposition mechanisms in degraded ecosystems as well as provide a scientific basis for improving species cycling and nutrient transformation efficiency in mining ecosystems.